The Intuitive Manager and the Concept of Strategic Leadership = Intuicyjny menedżer a koncepcja strategicznego przywództwa - Malewska, Kamila; Sajdak, Maja (Zielona Góra: Faculty of Economics and Management Press)
The aim of this paper is to show the consistency of an intuitive manager's traits and skills and a strategic leader?s attributes. The paper consists of three main parts. The first one presents the nature and evolution of the concept of leadership and contrasts the role of strategic leaders with the operational requirements of modern organizations. In the second part, we attempt to define the concept of intuition and characterize an intuitive manager. In the last section of the paper, a strategic leader's attributes and an intuitive manager's skills and characteristics are analyzed in order to show how these two categories converge.
Keywords: przywództwo strategiczne; menedżer intuicyjny; strategic leadership; intuitive manager